Organic solvent dispersion of titanium dioxide fine particles, method for producing the same, and use thereof

By using silane coupling agent and dispersant with alkaline adsorption groups in titanium dioxide fine particles, the problem of insufficient dispersion of titanium dioxide fine particles is solved, and a film with high transparency and high refractive index is achieved, which is suitable for optical and display applications.

CN114761358BActive Publication Date: 2025-04-08ISHIHARA SANGYO KAISHA LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080082689.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-19
Publication Date
2025-04-08
Estimated Expiration
2040-11-19

AI Technical Summary

Technical Problem

In the prior art, the dispersion of titanium dioxide particles in organic solvents is insufficient, resulting in insufficient transparency and refractive index in optical applications and display applications.

Method used

The dispersion of the titanium dioxide particles is improved by using a silane coupling agent and a dispersant having an alkaline adsorption group in the titanium dioxide particles.

Benefits of technology

The high dispersion of titanium dioxide fine particles in the organic solvent is achieved, forming a film with high visible light transmittance and high refractive index, and a high refractive index layer and anti-reflection film suitable for optical applications and displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003665543890000171
    Figure BDA0003665543890000171
  • Figure BDA0003665543890000191
    Figure BDA0003665543890000191
Patent Text Reader

Abstract

The present invention provides a dispersion obtained by highly dispersing titanium dioxide particles in an organic solvent and a method for producing the same. The dispersion comprises at least titanium dioxide particles, an organic solvent, a silane coupling agent, and a dispersant having a basic adsorption group, wherein the mass ratio of the dispersant to the silane coupling agent is 15% to 75% by mass. In addition, the total amount of the silane coupling agent and the dispersant is preferably 10% to 40% by mass relative to the mass ratio of the titanium dioxide particles. The dispersion is produced by dispersing the titanium dioxide particles, the specified amount of the silane coupling agent, and the dispersant having a basic adsorption group in an organic solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an organic solvent dispersion of titanium dioxide fine particles and a method for producing the same, as well as a coating composition comprising the organic solvent dispersion, and uses of a film comprising the organic solvent dispersion or the coating composition. Background Art

[0002] Titanium dioxide particles are useful materials having visible light transmittance, ultraviolet shielding properties, and a high refractive index. They are dispersed in an organic solvent to prepare an organic solvent dispersion or a coating composition, which is then applied or blown onto a substrate to form a film containing the titanium dioxide particles.

[0003] Titanium dioxide fine particles are used, for example, to form hard coatings, ultraviolet shielding films, etc., having high visible light transmittance (transparency) and high refractive index on the surface of synthetic resin lenses and films. In addition, anti-reflection films are provided on the display surfaces of flat panel displays (FPDs) such as liquid crystal displays (LCDs), plasma displays (PDPs), and electroluminescent displays (ELs) for the purpose of preventing reflections of light sources or faces, and titanium dioxide fine particles are used in the high refractive index layer.

[0004] Titanium dioxide particles are easy to aggregate if dispersed in an organic solvent. When a coating composition obtained by combining the aggregated titanium dioxide with a binder resin is used to form a film, visible light transmittance and the like are also reduced. Therefore, organic solvent dispersions obtained by highly dispersing titanium dioxide particles have been studied. For example, Patent Document 1 describes a titanium dioxide particle dispersion containing titanium dioxide particles having an average primary particle size of 2 to 80 nm and an average secondary particle size of 50 to 150 nm, a nonionic surfactant, and a glycol ether organic solvent. In addition, Patent Document 2 describes a transparent titanium dioxide organic sol, which includes titanium dioxide sol particles coated with a hydrated oxide of silicon, a dispersion medium of a mono-lower alkyl ether or a di-lower alkyl ether of ethylene glycol or propylene glycol, and a polymer dispersant having an amino group and a molecular weight of 5,000 to 50,000.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2014 / 132607 Pamphlet

[0008] Patent Document 2: Japanese Patent Application Publication No. 2009-227500 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the above-mentioned prior art, although the dispersibility of titanium dioxide particles has been improved, it is not sufficient when the film containing titanium dioxide particles is used for optical applications such as lenses, electronic devices such as various displays, etc., and a film with higher visible light transmittance (transparency) is required. Under such circumstances, an organic solvent dispersion of titanium dioxide particles with high dispersibility is still required.

[0011] Means for solving problems

[0012] The present inventors have conducted intensive studies to solve the above problems and have found that titanium dioxide fine particles can be highly dispersed in an organic solvent by using a silane coupling agent and a dispersant in combination in specific amounts, thereby completing the present invention.

[0013] That is, the present invention is as follows:

[0014] (1) An organic solvent dispersion of titanium dioxide particles, comprising titanium dioxide particles, an organic solvent, a silane coupling agent, and a dispersant having a basic adsorption group, wherein the mass ratio of the dispersant to the silane coupling agent is 15% to 75% by mass;

[0015] (2) The organic solvent dispersion of titanium dioxide fine particles according to (1), wherein the total amount of the silane coupling agent and the dispersant is 10% by mass to 40% by mass relative to the mass of the titanium dioxide fine particles;

[0016] (3) The organic solvent dispersion of titanium dioxide fine particles according to (1) or (2), wherein the surface of the titanium dioxide fine particles is coated with aluminum oxide and / or hydroxide;

[0017] (4) The organic solvent dispersion of titanium dioxide fine particles according to any one of (1) to (3), wherein the titanium dioxide fine particles have rutile crystals;

[0018] (5) A method for producing an organic solvent dispersion of titanium dioxide fine particles, which comprises dispersing titanium dioxide fine particles, a silane coupling agent, and a dispersant having a basic adsorption group in an organic solvent;

[0019] (6) The production method according to (5), wherein the mass ratio of the dispersant having a basic adsorption group to the silane coupling agent is 15 mass % to 75 mass %;

[0020] (7) The production method according to (5) or (6), wherein the dispersion is a wet dispersion using a bead medium;

[0021] (8) A coating composition comprising at least the organic solvent dispersion of titanium dioxide fine particles according to any one of (1) to (4) and a binder resin.

[0022] (9) A coating film comprising the organic solvent dispersion of titanium dioxide fine particles according to any one of (1) to (4) or the coating composition according to (8).

[0023] Effects of the Invention

[0024] According to the present invention, the titanium dioxide fine particles can be highly dispersed in the organic solvent by using a silane coupling agent and a dispersant having a basic adsorption group in combination in specific amounts as a dispersion containing titanium dioxide fine particles and an organic solvent.

[0025] According to the present invention, in addition to the above, for example, the following effects can be achieved.

[0026] When the organic solvent dispersion is used, a film having high visible light transmittance (transparency) can be formed. Specifically, a high refractive index layer having high transparency can be formed, and an antireflection film having higher transparency can be produced. DETAILED DESCRIPTION

[0027] The organic solvent dispersion of the present invention contains titanium dioxide particles. The average primary particle size of the titanium dioxide particles is preferably 3 to 200 nm (3 nm or more and 200 nm or less), more preferably 5 to 100 nm (5 nm or more and 100 nm or less), and further preferably 10 to 100 nm (10 nm or more and 100 nm or less). Generally speaking, titanium dioxide particles having such an average primary particle size have higher visible light transmittance than titanium dioxide particles having a larger average primary particle size (for example, titanium dioxide particles having an average primary particle size of about 0.2 to 0.5 μm for pigment purposes). Therefore, by using titanium dioxide particles having the above-mentioned average primary particle size, an organic solvent dispersion with higher transmittance can be manufactured. Regarding the average primary particle size of titanium dioxide particles, the particle size of 200 randomly selected particles is measured under an electron microscope and calculated as the average value of the particle size (also referred to as "electron micrograph method" in this application).

[0028] The shape of the titanium dioxide particles is not particularly limited, and titanium dioxide particles of any shape such as spherical, rod-shaped, needle-shaped, spindle-shaped, plate-shaped, etc. can be used. For the above average primary particle size in the case of shapes other than spherical, in the case of rod-shaped, needle-shaped, spindle-shaped particles, it is specified by the average length of the short axis side, and in the case of plate-shaped particles, it is specified by the average length of the diagonal line of the surface.

[0029] There is no particular limitation on the crystal structure of titanium dioxide particles, and titanium dioxide particles of anatase type, rutile type, brookite type, etc. can be used. Among them, rutile type has lower photocatalytic activity and higher refractive index than anatase type, so in order to make the film more effectively have high light resistance and high refractive index, it is preferred to use titanium dioxide particles with rutile crystals. In addition to titanium dioxide (TiO2), titanium dioxide particles can also be composed of compounds represented by metatitanic acid (TiO2·nH2O) and orthotitanic acid (Ti(OH)4).

[0030] Titanium dioxide microparticles can be manufactured by various well-known methods. For example, the following methods can be used: a method in which an aqueous titanium tetrachloride solution is neutralized and hydrolyzed with an alkali, and the resulting hydrous titanium dioxide is calcined (also referred to as a "calcination method" in this application); a method in which the hydrous titanium dioxide obtained by hydrolyzing an aqueous titanium oxysulfate solution is heated with sodium hydroxide, and the resulting reaction product is heated and matured with an acid; or a method in which an aqueous titanium tetrachloride solution is neutralized and hydrolyzed with an alkali (also referred to as a "wet method" in this application). Generally speaking, spherical titanium dioxide microparticles can be obtained by the above-mentioned calcination method, and spindle-shaped titanium dioxide microparticles can be obtained by the above-mentioned wet method. In addition, both the calcination method and the wet method can obtain rutile-type titanium dioxide microparticles.

[0031] The spherical titanium dioxide particles obtained by the calcination method are more preferred because the crystallinity is improved and the photocatalytic activity is suppressed by calcination, so the film can have high light resistance more effectively. In addition, for the titanium dioxide particles obtained by the wet method, it is usually not dried or calcined, and the manufactured titanium dioxide particle aqueous dispersion is dispersed in the organic solvent by solvent replacement, but in the present invention, it is more preferred to dry and / or calcine to disperse the titanium dioxide powder directly in the organic solvent. If drying and / or calcination is performed, the water contained becomes less, and the water attached to the titanium dioxide particles also becomes less, so it is easy to disperse in the organic solvent. The drying temperature is preferably about 80 to 150°C, and the calcination temperature is preferably about 150 to 400°C.

[0032] As for titanium dioxide particles, the surface of the particles can be coated with other inorganic compounds. The coated inorganic compound can use a known surface treatment material, for example, an oxide and / or hydroxide of at least one of zinc, titanium, cerium, iron, silicon and aluminum can be used. It is more preferred that the surface of the titanium dioxide particles is coated with an oxide and / or hydroxide of aluminum. The coating amount is preferably 1% to 30% (1% or more and 30% or less) based on the mass of TiO2. By coating with inorganic compounds, the photocatalytic activity of titanium dioxide can be more effectively suppressed, and the film can have higher light resistance.

[0033] The organic solvent dispersion of the present invention comprises an organic solvent. The organic solvent used is not particularly limited, and a known organic solvent can be used. From the viewpoints of compatibility with the binder resin, dispersibility of the titanium dioxide particles, and coating properties on the substrate, ketones or (poly) alkylene glycol monoalkyl ethers are preferred.

[0034] Examples of the ketones include methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, 2-heptanone, 3-heptanone, diacetone alcohol (4-hydroxy-4-methylpentane-2-one), and 4-hydroxy-4-methylhexane-2-one.

[0035] Examples of the (poly)alkylene glycol monoalkyl ethers include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol mono-n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol mono-n-butyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, propylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, and the like.

[0036] The organic solvent dispersion of the present invention contains a silane coupling agent. A silane coupling agent refers to an organic silicon compound having both an organic functional group X and a hydrolyzable group OR in one molecule. O in the hydrolyzable group OR is an oxygen atom, and R generally represents a hydrogen atom or an alkyl group having 1 to 22 carbon atoms (1 or more and 22 or less). The alkyl group may be any of a linear, branched or cyclic group. When there are multiple hydrolyzable groups OR in the molecule of the silane coupling agent, R may be the same or different from each other. The organic functional group X is generally preferably selected from at least one of methacryloyl, acryl, vinyl, epoxy, amino, mercapto, thioether, isocyanate, etc. When there are multiple organic functional groups X in the molecule of the silane coupling agent, X may be the same or different from each other.

[0037] In the organic solvent dispersion, the silane coupling agent functions as a dispersing aid for facilitating deagglomeration of the titanium dioxide fine particles in an aggregated state.

[0038] As such silane coupling agent, methacryl silane or acryl silane, vinyl silane, epoxy silane, etc. can be mentioned. Specifically, as methacryl silane, 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, 3-methacryloxypropyl triethoxy silane, methacryloxy octyl trimethoxy silane can be mentioned. In addition, as acryl silane, 3-acryloxypropyl trimethoxy silane can be mentioned. In addition, as vinyl silane, vinyl trimethoxy silane, vinyl triethoxy silane, octenyl trimethoxy silane can be mentioned. As epoxy silane, glycidoxy propyl trimethoxy silane and glycidoxy octyl trimethoxy silane can be mentioned.

[0039] The organic solvent dispersion of the present invention contains a dispersant having a basic adsorption group. In the organic solvent dispersion of the present invention, the dispersant inhibits the re-agglomeration of the titanium dioxide particles in the organic solvent after deagglomeration, and helps to maintain the titanium dioxide particles in a dispersed state (stabilization). In the present invention, a dispersant having a basic adsorption group is used as a dispersant, and by using a dispersant having a basic adsorption group and a silane coupling agent in combination, the surface of the titanium dioxide particles can be reliably protected, and dispersion stabilization can be achieved.

[0040] As dispersants having basic adsorption groups, primary amines, secondary amines, tertiary amines and quaternary ammonium or their salts can be cited. These amine dispersants contain amino groups as basic adsorption groups, or partial structures obtained by replacing one or more hydrogens of the amino groups with alkyl groups, etc. In the case where the dispersant has these basic adsorption groups, the amine value of the dispersant can be determined by the following method. Dispersants with this value greater than 5 mgKOH / g have sufficiently high alkalinity and can obtain the desired dispersing effect. The amine value is a value in which the amount of alkali per 1 g of solid content in the dispersant sample after removing the solvent is expressed as the mass of equivalent KOH (mgKOH / g). The amine value can be determined by the known methods specified in ASTM D2074, JIS K 7237, etc., and specifically by the following method.

[0041] (Determination method of amine value)

[0042] Accurately weigh 0.5-1.5 g of the dispersant sample in a 100 mL beaker and dissolve it in 50 mL of acetic acid. Use an automatic titrator equipped with a pH electrode to neutralize and titrate the solution with 0.1 mol / L HClO4 (perchloric acid) acetic acid solution. The inflection point of the titration pH curve is set as the titration endpoint, and the amine value is calculated by the following formula.

[0043] Amine value [mgKOH / g] = (561×V) / (W×S)

[0044] [W represents the amount of the dispersant sample weighed [g], V represents the titration amount at the titration endpoint [mL], and S represents the solid content concentration of the dispersant sample [mass %].]

[0045] As the dispersant having a basic adsorption group, an amine-based dispersant having an amino group is preferred, and for example, commercially available products such as DISPERBYK (registered trademark)-163 (manufactured by BYK Chemie), Solsperse (registered trademark) 20000, Solsperse (registered trademark) 39000, Solsperse (registered trademark) 56000 (manufactured by Lubrizol Japan Ltd.), 2-diethylaminoethyl methacrylate, etc. can be used.

[0046] In the organic solvent dispersion of the present invention, the mass ratio of the dispersant having a basic adsorption group to the silane coupling agent is 15% to 75% by mass (15% to 75% by mass). The titanium dioxide particles are deagglomerated by the silane coupling agent to form a dispersed state, and the dispersant having a basic adsorption group helps maintain this state (stabilization). Therefore, the mass ratio of the dispersant having a basic adsorption group to the silane coupling agent can be set to 15% to 75% by mass. On the other hand, if the mass ratio of the dispersant having a basic adsorption group to the silane coupling agent is greater than 75% by mass, the content of the silane coupling agent decreases, and there is a tendency to damage its function, that is, to make the titanium dioxide particles in a coagulated state in the organic solvent easy to deagglomerate by wet dispersion, etc., and its function cannot be fully exerted. If the mass ratio of the dispersant having a basic adsorption group is less than the above-mentioned 15% by mass, the content of the dispersant decreases, and its function cannot be fully exerted. Therefore, the mass ratio of the dispersant having a basic adsorption group to the silane coupling agent is 15% to 75% by mass, more preferably 15% to 70% by mass (15% to 70% by mass), and further preferably 20% to 70% by mass (20% to 70% by mass).

[0047] In the organic solvent dispersion of the present invention, the total amount of silane coupling agent and dispersant is preferably 10% to 40% by mass (10% to 40% by mass) relative to the mass ratio of titanium dioxide particles. By making the silane coupling agent and the dispersant having a basic adsorption group contain more than 10% by mass relative to the titanium dioxide particles, the above effect can be reliably exerted. On the other hand, even if more than 40% by mass is contained, the above effect reaches the upper limit. In addition, if the content of the organic compound of the silane coupling agent and the dispersant having a basic adsorption group becomes more, the hardness of the film becomes weaker, or the refractive index decreases, so it is preferably 40% to 40% by mass. Thus, the total amount of the silane coupling agent and the dispersant having a basic adsorption group is more preferably 15% to 35% by mass (15% to 35% by mass) relative to the mass ratio of titanium dioxide particles, and more preferably 15% to 30% by mass (15% to 30% by mass).

[0048] The organic solvent dispersion of the present invention can be prepared by mixing and dispersing the titanium dioxide particles, the silane coupling agent and the dispersant having a basic adsorption group in an organic solvent, so that the titanium dioxide particles are dispersed in the organic solvent. During the dispersion, in addition to the silane coupling agent and the dispersant having a basic adsorption group, a dispersing aid, a dispersion stabilizer, a defoaming agent, a thickener, inorganic oxide particles other than the titanium dioxide particles, etc. can also be added.

[0049] The above-mentioned dispersion can use a known dispersing machine. For example, a paint shaker or dissolver, a high-speed stirrer, a mixing machine, an ultrasonic disperser, a high-pressure homogenizer, a ball mill or a bead mill, a sand mill, a horizontal medium mill dispersing machine, a colloid mill, etc. can be used. From the viewpoint of dispersibility, it is preferred to use a bead medium when dispersing. When a bead mill is used, a bead medium with a diameter of less than 1 mm is preferred, and a bead medium with a diameter of less than 0.5 mm is more preferred. In the above-mentioned dispersion, the intensity of the dispersion varies according to the dispersing device and the type of medium used. Therefore, the dispersion time is appropriately adjusted according to the dispersing device and the type of medium.

[0050] The above dispersion can be carried out multiple times. For example, it is preferably carried out in a pre-dispersion and a formal dispersion. Through the pre-dispersion, the surface of the titanium dioxide particles is wetted, and the air layer on the surface is replaced with the organic solvent, so that in the subsequent formal dispersion, the dispersion is rapidly promoted. As a result, the dispersibility of the titanium dioxide particles in the organic solvent can be effectively improved. In the formal dispersion, it is preferred to use a bead medium with a smaller diameter than the pre-dispersion. By doing so, the dispersibility of the titanium dioxide particles in the organic solvent can be further improved.

[0051] The coating composition of the present invention comprises the organic solvent dispersion of the titanium dioxide particles and a binder resin. Since the organic solvent dispersion of the present invention has high transmittance, a coating film having high visible light transmittance (transparency) can be formed by using the coating composition using the organic solvent dispersion.

[0052] As the binder resin for coating composition, as long as the stability, high refractive index and visible light transmittance (transparency) of the film obtained by the coating composition are ensured, there is no particular limitation. As the binder resin, for example, alkyd resin, acrylic resin, melamine resin, carbamate resin, epoxy resin, silicon resin, etc. can be used. In addition, polyester resin, polyamic acid resin, polyimide resin, styrene maleic acid resin, styrene maleic anhydride resin, etc. can also be used. In addition, various acrylic acid monomers and acrylate monomers can also be applied. About the resin and monomer that are particularly preferred as the binder resin, carbamate resin, acrylic acid monomer, polyamic acid resin, polyimide resin, styrene maleic acid resin, styrene maleic anhydride resin can be cited. The binder resin can be used alone or in combination of two or more.

[0053] In addition, the coating composition may contain various additives in addition to the organic solvent dispersion of titanium dioxide particles and the binder resin, such as dispersants, pigments, fillers, aggregates, thickeners, flow control agents, leveling agents, curing agents, crosslinking agents, curing catalysts, etc.

[0054] The coating composition of the present invention can be prepared by mixing the organic solvent dispersion of titanium dioxide fine particles, the binder resin, and the additives as required. In the mixing step, for example, the dissolver or high-speed stirrer is preferably used.

[0055] The organic solvent dispersion or coating composition of the present invention is applied to a substrate, dried and / or fired as required, so that a film can be formed on the substrate. The substrate is not particularly limited, and various materials such as glass, polymer, ceramic, metal can be used. The coating method is not particularly limited, and known methods can be used. For example, methods such as a method for coating using a spin coater, a dip coater, a die coater, a slit coater, a rod coater, a gravure coater, etc., LB (Langmuir-Blodgett) film method, a self-assembly method, and a spray coating method can be cited.

[0056] There are no particular restrictions on the drying method and the calcining method, and known methods can be used. For example, heat drying under normal pressure or reduced pressure, natural drying, etc. are mentioned. The heating method in heat drying and calcining is also not particularly limited, and for example, a method of heating using a hot plate, an oven, etc. can be mentioned. The drying temperature is preferably about 80 to 150°C, and the calcining temperature is preferably about 150 to 400°C.

[0057] The thickness of the film can be appropriately set according to the purpose, but for example, it is preferably 0.005μm to 2μm (above 0.005μm and below 2μm), and more preferably 0.01μm to 1μm (above 0.01μm and below 1μm). Regarding the visible light transmittance of the film, it can be measured using a haze meter as haze. The haze is also affected by the film thickness, but is preferably below 5%, more preferably below 2.5%, and further preferably below 1.5%. In addition, for using the film as a high refractive index layer, the refractive index of the film is preferably above 1.60, and preferably above 1.80. The refractive index can be measured and calculated by an ellipsometer.

[0058] The film formed on the substrate can be stacked in multiple layers. In the case of multi-layer stacking, each layer can be a homogeneous film or a combination of different films. In addition, by alternately stacking the above-mentioned high refractive index layer and the low refractive index layer on the substrate, an anti-reflection film can be formed on the substrate. The anti-reflection film can be any composition as long as it comprises the above-mentioned high refractive index layer, for example, it can be an anti-reflection film having a high refractive index layer and a low refractive index layer on the substrate in sequence, or it can be an anti-reflection film having a low refractive index layer, a high refractive index layer and a low refractive index layer on the substrate in sequence. In such a layer constitution, by adjusting the film thickness and the refractive index of each layer, a desired anti-reflection film can be designed.

[0059] Example

[0060] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.

[0061] (Example 1)

[0062] 20 parts by mass of TTO-51A (manufactured by Ishihara Sangyo Co., Ltd.) (powder), which is titanium dioxide fine particles having a rutile crystal form and an average primary particle size of 20 nm produced by the above-mentioned "calcination method" and surface-treated with aluminum hydroxide (Al(OH)3), 2.4 parts by mass of 3-methacryloxypropyltriethoxysilane KBM-503 (manufactured by Shin-Etsu Silicone Co.) as a silane coupling agent, 0.6 parts by mass of Solsperse (registered trademark) 20000 (manufactured by Lubrizol Japan Ltd., amine value 32 mgKOH / g) as an amine dispersant, and 77 parts by mass of methyl ethyl ketone (MEK) as an organic solvent were placed in a mixing container and wet dispersed for 4 hours using a paint shaker (1400-0H manufactured by Red Devil Co.) using zirconium oxide beads having a diameter of 0.1 mm. The obtained dispersion was centrifuged at 2400 G for 13 minutes using a centrifuge (H-19α manufactured by KOKUSAN Corporation) to precipitate coarse particles and recover the supernatant to obtain an organic solvent dispersion of titanium dioxide fine particles.

[0063] The mass ratio of the amine dispersant in the organic solvent dispersion was 25% by mass relative to the silane coupling agent. The silane coupling agent used was 12% by mass, and the amine dispersant was 3% by mass relative to the titanium dioxide fine particles, and the total amount of the two was 15% by mass.

[0064] (Example 2)

[0065] In Example 1, the mass ratio of the amine dispersant in the organic solvent dispersion is changed to 66.7 mass % relative to the silane coupling agent. Specifically, the feed ratio of each material is changed to 5 mass parts of titanium dioxide particles, 0.9 mass parts of silane coupling agent, 0.6 mass parts of amine dispersant, and 93.5 mass parts of organic solvent. The wet dispersion time is set to 3 hours, and the titanium dioxide particles use the unfired titanium dioxide particles (powder) described later. In addition, the organic solvent dispersion of titanium dioxide particles is obtained in the same manner as in Example 1.

[0066] The amount of the silane coupling agent used was 18% by mass and the amount of the amine dispersant used was 12% by mass based on the titanium dioxide fine particles in the organic solvent dispersion, and the total amount of the two was 30% by mass.

[0067] The titanium dioxide fine particles used in Example 2 were produced as follows.

[0068] Titanium tetrachloride aqueous solution is added to tin tetrachloride aqueous solution in a ratio of SnO2 / TiO2=1, and heated and hydrolyzed at 100°C for 1 hour to obtain a slurry of rutile titanium oxide (33g / L) containing tin (150g in terms of rutile titanium oxide containing tin). Next, while cooling the slurry to 80°C, neutralize it with sodium hydroxide aqueous solution (20%) and adjust the pH to 10.0. Next, sodium aluminate aqueous solution (0.6L) is added in a manner that converts to Al2O3 to become 15% by mass of the above-mentioned rutile titanium dioxide, and then, it is neutralized with sulfuric acid aqueous solution (5%) to pH7.0 to precipitate aluminum hydroxide, thereby obtaining a rutile titanium dioxide slurry surface-treated with aluminum hydroxide. After the slurry is cooled to room temperature, it is filtered with a suction filter and washed with water and then dried at 150°C to obtain unfired titanium dioxide particles.

[0069] (Example 3)

[0070] In Example 1, the organic solvent was changed to propylene glycol monomethyl ether acetate (PGMEA). In addition, the feed ratio of each material was changed to 24 parts by mass of titanium dioxide particles, 2.88 parts by mass of silane coupling agent, 0.72 parts by mass of amine dispersant, and 72.4 parts by mass of organic solvent. Otherwise, the same operation as in Example 1 was performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0071] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0072] (Example 4)

[0073] In Example 1, the amine dispersant was changed to 2-diethylaminoethyl methacrylate (DEM) (amine value (theoretical value) 300 mgKOH / g). In addition, the charging ratio of each material was changed to 20 parts by mass of titanium dioxide particles, 4.8 parts by mass of silane coupling agent, 1.2 parts by mass of amine dispersant, and 74 parts by mass of organic solvent. Otherwise, the same operation as in Example 1 was performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0074] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 24 mass % and the amine dispersant was 6 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 30 mass %.

[0075] (Example 5)

[0076] In Example 3, the silane coupling agent was changed to 3-acryloxypropyltrimethoxysilane KBM-5103 (manufactured by Shin-Etsu Silicone Co.). In addition, the charging ratio of each material was changed to 20 parts by mass of titanium dioxide particles, 2.4 parts by mass of silane coupling agent, 0.6 parts by mass of amine dispersant, and 77 parts by mass of organic solvent. Otherwise, the same operation as in Example 3 was performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0077] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0078] (Example 6)

[0079] In Example 3, the silane coupling agent was changed to methacryloxyoctyl trimethoxysilane KBM-5803 (manufactured by Shin-Etsu Silicone Co.). In addition, the charging ratio of each material was changed to 20 parts by mass of titanium dioxide particles, 2.4 parts by mass of silane coupling agent, 0.6 parts by mass of amine dispersant, and 77 parts by mass of organic solvent. Otherwise, the same operation as in Example 3 was performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0080] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0081] (Example 7)

[0082] In Example 3, the silane coupling agent was changed to octenyl trimethoxysilane KBM-1083 (manufactured by Shin-Etsu Silicone Co.), and the amine dispersant was changed to DISPERBYK (registered trademark) -163 (manufactured by BYK Chemie, with an active ingredient of 45%, an amine value of 10 mgKOH / g). In addition, the feed ratio of each material was changed to 20 parts by mass of titanium dioxide particles, 2.4 parts by mass of silane coupling agent, 0.6 parts by mass of amine dispersant, and 77 parts by mass of organic solvent. In addition, the same operation as in Example 3 was performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0083] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0084] (Example 8)

[0085] In Example 3, the silane coupling agent was changed to octenyl trimethoxysilane KBM-1083 (Shin-Etsu Silicone Co.). In addition, the charging ratio of each material was changed to 23 parts by mass of titanium dioxide particles, 2.8 parts by mass of silane coupling agent, 0.7 parts by mass of amine dispersant, and 73.5 parts by mass of organic solvent. The wet dispersion time was set to 6 hours and 40 minutes. In addition, the same operation as in Example 3 was performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0086] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0087] (Example 9)

[0088] In Example 3, the titanium dioxide particles are changed to TTO-55B (made by Ishihara Sangyo Co., Ltd.) (powder). It should be noted that TTO-55B is manufactured by the "calcination method" in the same manner as TTO-51A, and the crystal form is rutile, and surface-treated with aluminum hydroxide (Al(OH)3), and the average primary particle size is 40nm. In addition, the feed ratio of each material is changed to 23 parts by mass of titanium dioxide particles, 2.8 parts by mass of silane coupling agent, 0.7 parts by mass of amine dispersant, and 73.5 parts by mass of organic solvent. The wet dispersion time is set to 6 hours and 40 minutes. In addition, the same operation as Example 3 is performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0089] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0090] (Example 10)

[0091] In Example 3, titanium dioxide particles are changed to TTO-55D (made by Ishihara Sangyo Co., Ltd.) (powder). It should be noted that TTO-55D is manufactured by "sintering method" in the same way as TTO-51A, and its crystal form is rutile, and in addition to aluminum hydroxide (Al(OH)3), it is also surface treated with zirconium oxide (ZrO2), and the average primary particle size is 40nm. In addition, the feed ratio of each material is changed to 23 parts by mass of titanium dioxide particles, 2.8 parts by mass of silane coupling agent, 0.7 parts by mass of amine dispersant, and 73.5 parts by mass of organic solvent. The wet dispersion time is set to 6 hours and 40 minutes. In addition, the same operation as Example 3 is performed to obtain an organic solvent dispersion of titanium dioxide particles.

[0092] The mass ratio of the amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0093] (Example 11)

[0094] In Example 1, the titanium dioxide fine particles were changed to TTO-51N (manufactured by Ishihara Sangyo Co., Ltd.). It should be noted that TTO-51N is manufactured by the "calcination method" in the same manner as TTO-51A, has a rutile crystal form, and an average primary particle size of 20 nm. The difference from TTO-51A is that the surface treatment of aluminum hydroxide (Al(OH)3) is omitted.

[0095] In addition, propylene glycol monomethyl ether (PGME) was used as the organic solvent, and the feed ratio of each material was changed to 26.3 parts by weight of titanium dioxide particles, 4.4 parts by weight of silane coupling agent, 0.8 parts by weight of amine dispersant, and 68.5 parts by weight of organic solvent. The wet dispersion time was set to 8 hours. In addition, the same operation as in Example 1 was performed to obtain a dispersion of titanium dioxide particles.

[0096] The mass ratio of the amine dispersant in the organic solvent dispersion was 18% by mass relative to the silane coupling agent. In addition, the silane coupling agent used was 17% by mass and the amine dispersant was 3% by mass relative to the titanium dioxide fine particles, and the total amount of the two was 20% by mass.

[0097] (Comparative Example 1)

[0098] In Example 1, the addition of the amine dispersant was omitted. That is, the charging ratio of each material was changed to 20 parts by mass of titanium dioxide fine particles, 3 parts by mass of silane coupling agent, and 77 parts by mass of organic solvent. Otherwise, the same operation as in Example 1 was carried out to obtain an organic solvent dispersion of titanium dioxide fine particles.

[0099] The mass ratio of the amine dispersant in the organic solvent dispersion was 0 mass % relative to the silane coupling agent. In addition, the silane coupling agent was used in an amount of 15 mass % relative to the titanium dioxide fine particles.

[0100] (Comparative Example 2)

[0101] In Example 1, the amine dispersant was replaced with BYK (registered trademark)-111 (manufactured by BYK Chemie) which is a (non-amine) dispersant having substantially no basic adsorption group and an amine value of less than 1. The same operation as in Example 1 was performed except for this to obtain an organic solvent dispersion of titanium dioxide fine particles.

[0102] The mass ratio of the non-amine dispersant in the organic solvent dispersion was 25 mass % relative to the silane coupling agent. In addition, the silane coupling agent used was 12 mass % and the non-amine dispersant was 3 mass % relative to the titanium dioxide fine particles, and the total amount of the two was 15 mass %.

[0103] (Comparative Example 3)

[0104] In Example 1, the mass ratio of the amine dispersant in the organic solvent dispersion was changed to 100 mass% relative to the silane coupling agent. Specifically, as the amine dispersant, DISPERBYK (registered trademark) -142 (manufactured by BYK Chemie, with an active ingredient of 60 mass% and an amine value of 43 mgKOH / g) was used, and the charging ratio of each material was changed to 20 mass parts of titanium dioxide particles, 1.5 mass parts of silane coupling agent, 1.5 mass parts of amine dispersant, and 77 mass parts of organic solvent. In addition, the organic solvent dispersion of titanium dioxide particles was obtained in the same manner as in Example 1.

[0105] The silane coupling agent and the amine dispersant used were 7.5% by mass and 7.5% by mass, respectively, based on the titanium dioxide fine particles in the organic solvent dispersion, and the total amount of the two was 15% by mass.

[0106] (Comparative Example 4)

[0107] In Example 1, the addition of the silane coupling agent was omitted. That is, the feed ratio of each material was changed to 20 parts by mass of titanium dioxide fine particles, 1 part by mass of the amine dispersant, and 79 parts by mass of the organic solvent. Otherwise, the same operation as in Example 1 was performed to obtain an organic solvent dispersion of titanium dioxide fine particles.

[0108] The mass ratio of the amine dispersant in the organic solvent dispersion to the silane coupling agent is infinite. The amine dispersant used is 5 mass % relative to the titanium dioxide fine particles.

[0109] <Evaluation of dispersibility>

[0110] In the manufacture of the organic solvent dispersion of the above-mentioned embodiment and comparative example, when the coarse particles are precipitated and the supernatant is recovered by centrifugation after wet dispersion, the solid content concentration of the dispersion before centrifugation is compared with the solid content concentration of the dispersion (organic solvent dispersion) after centrifugation. The case where there is almost no difference in the solid content concentration of the two (specifically, the case where the solid content concentration of the dispersion (organic solvent dispersion) after centrifugation is 80% or more of the solid content concentration of the dispersion before centrifugation) is evaluated as excellent dispersibility ("0"), and the case where the solid content concentration of the dispersion (organic solvent dispersion) after centrifugation is less than 80% of the solid content concentration of the dispersion before centrifugation is evaluated as insufficient dispersibility ("×"). The evaluation results are shown in Table 1.

[0111] <Evaluation of transmittance of organic solvent dispersion>

[0112] For the organic solvent dispersions of the embodiments and comparative examples, the same organic solvent as the dispersion medium was used and diluted in such a way that the filler concentration became 12 g / L. It was fed into a sample cell with an optical path length of 1 mm as a measurement sample, and the transmittance was measured with a spectrophotometer (V-770: manufactured by JASCO Corporation). Regarding the transmittance, the average value of the transmittance at a wavelength of 380-780 nm was measured. The measurement results are shown in Table 1. It should be noted that the organic solvent dispersions of Comparative Examples 1 to 4 could not adjust the concentration due to sedimentation, and the transmittance could not be measured.

[0113] [Table 1]

[0114]

[0115] As shown in Table 1, it can be seen that in Examples 1 to 11 in which the mass ratio of the dispersant having a basic adsorption group to the silane coupling agent is within the range of 15 mass % to 75 mass %, the dispersibility of the titanium dioxide particles in the organic solvent is higher than that of any of Comparative Examples 1 to 4 that do not meet the range, and the average value of the transmittance at a wavelength of 380-780 nm also shows a higher value. For example, in an organic solvent dispersion of titanium dioxide particles, even if a silane coupling agent and a dispersant having a basic adsorption group are contained together, when the mass ratio of the dispersant to the silane coupling agent is greater than the above range (Comparative Example 3), it is difficult to disperse the titanium dioxide particles in the organic solvent.

[0116] In addition, as shown in Table 1, in the organic solvent dispersion of titanium dioxide particles in Comparative Example 1 lacking a dispersant having a basic adsorption group or Comparative Example 4 lacking a silane coupling agent, it was difficult to disperse the titanium dioxide particles in the organic solvent. In addition, in Comparative Example 2 using a dispersant having no basic adsorption group instead of a dispersant having a basic adsorption group, it was also difficult to disperse.

[0117] As described above, it can be seen that in the organic solvent dispersion of titanium dioxide particles of this embodiment, by containing a silane coupling agent and a dispersant having a basic adsorption group together, and setting the mass ratio of the dispersant to the silane coupling agent in an appropriate range (15% by mass to 75% by mass), high dispersibility is exhibited, and the average value of the transmittance of the organic solvent dispersion at a wavelength of 380-780nm also shows a high value.

[0118] <Preparation of coating composition>

[0119] (Production Example 1)

[0120] An ultraviolet-curable coating composition is prepared by mixing 86.6 parts by mass of an organic solvent dispersion of titanium dioxide particles of Example 8 (solid content 21.8%), 8.9 parts by mass of dipentaerythritol hexaacrylate (M-405 manufactured by Toagosei Co., Ltd.), and 4.5 parts by mass of PGMEA solutions of IRGACURE (registered trademark)-184 and Omnirad (registered trademark) TPO (each with a concentration of 3% by mass).

[0121] (Production Example 2)

[0122] An ultraviolet-curable coating composition is prepared by mixing 86.3 parts by mass of an organic solvent dispersion of titanium dioxide particles of Example 9 (solid content: 22.0%), 9.1 parts by mass of dipentaerythritol hexaacrylate (M-405 manufactured by Toagosei Co., Ltd.), and 4.6 parts by mass of PGMEA solutions of IRGACURE (registered trademark)-184 and Omnirad (registered trademark) TPO (each with a concentration of 3% by mass).

[0123] (Production Example 3)

[0124] An ultraviolet-curable coating composition is prepared by mixing 87.3 parts by mass of an organic solvent dispersion of titanium dioxide particles of Example 10 (solid content 21.3%), 8.5 parts by mass of dipentaerythritol hexaacrylate (M-405 manufactured by Toagosei Co., Ltd.), and 4.2 parts by mass of PGMEA solutions of IRGACURE (registered trademark)-184 and Omnirad (registered trademark) TPO (each with a concentration of 3% by mass).

[0125] (Production Example 4)

[0126] An ultraviolet-curable coating composition is prepared by mixing 45.9 parts by weight of an organic solvent dispersion of titanium dioxide particles of Example 11 (solid content 29.7%), 20.3 parts by weight of dipentaerythritol hexaacrylate (M-405 manufactured by Toagosei Co., Ltd.), 10.1 parts by weight of an isopropanol solution of IRGACURE (registered trademark)-184 (10% by mass), and 23.6 parts by weight of PGME.

[0127] <Measurement of the refractive index, etc. of the film>

[0128] The coating liquids of the above-mentioned manufacturing examples 1, 2, and 4 were applied to a glass substrate, pre-dried at 80° C. for 5 minutes, and then cured by irradiation with a high-pressure mercury lamp to form three films of different film thicknesses. In addition, the coating liquid of the above-mentioned manufacturing example 3 was applied to a PET film (A4100 manufactured by Toyobo Co., Ltd.) by spin coating, pre-dried at 80° C. for 5 minutes, and then cured by irradiation with a high-pressure mercury lamp to form films of three different film thicknesses.

[0129] The haze of the obtained film was measured with a haze meter (NDH-5000, manufactured by Nippon Denshoku Industries Co., Ltd.), and the film thickness and the refractive index at a measurement wavelength of 589 nm were measured with an ellipsometer (SmartSE, manufactured by Horiba, Ltd.).

[0130] [Table 2]

[0131]

[0132] As shown in Table 2, the coating composition of the present invention can form a film having a small haze and a large refractive index. Specifically, a film having a haze of 1.5% or less and a refractive index of 1.6 or more at a measurement wavelength of 589 nm can be formed.

[0133] Industrial Applicability

[0134] If the organic solvent dispersion of titanium dioxide particles of the present invention is used, a high film of visible light transmittance (transparency) can be formed. Specifically, a hard coat layer, an ultraviolet shielding film, etc. with high visible light transmittance (transparency) and high refractive index can be formed on the surface of a synthetic resin lens or film. In addition, the manufacture of high refractive index layers, anti-reflection films, etc., which require further transparency, such as liquid crystal displays (LCDs), flat panel displays (FPDs), etc., can be suitably used.

Claims

1. An organic solvent dispersion of titanium dioxide particles, comprising titanium dioxide particles, an organic solvent, a silane coupling agent, and a dispersant having a basic adsorption group, The mass ratio of the dispersant to the silane coupling agent is 15 mass % to 75 mass %, The total amount of the silane coupling agent and the dispersant having a basic adsorption group is 10% to 40% by mass relative to the mass ratio of the titanium dioxide fine particles. The titanium dioxide fine particles have rutile crystals.

2. The organic solvent dispersion of titanium dioxide fine particles according to claim 1, wherein The surfaces of the titanium dioxide fine particles are coated with aluminum oxide and / or hydroxide.

3. A method for producing an organic solvent dispersion of titanium dioxide particles, comprising dispersing titanium dioxide particles, a silane coupling agent, and a dispersant having a basic adsorption group in an organic solvent. The mass ratio of the dispersant to the silane coupling agent is 15 mass % to 75 mass %, The total amount of the silane coupling agent and the dispersant having a basic adsorption group is 10% to 40% by mass relative to the mass ratio of the titanium dioxide fine particles. The titanium dioxide fine particles have rutile crystals.

4. The manufacturing method according to claim 3, wherein: The dispersion is a wet dispersion using a bead medium. 5 . A coating composition comprising at least the organic solvent dispersion of titanium dioxide fine particles according to claim 1 or 2 and a binder resin. 6 . A coating film comprising the organic solvent dispersion of titanium dioxide fine particles according to claim 1 or 2 or the coating composition according to claim 5 .

Citation Information

Patent Citations

  • Transparent titanium oxide organosol, coating composition with the same blended, optical base material

    JP2009227500A

  • Liquid dispersion of titanium oxide particles, coating agent composition, and antibacterial / antiviral member

    WO2014132607A1

  • Telescopic shaft

    JP2007139091A

  • Composite resin composition

    JP2011116943A

  • Inner surface antireflection black coating material for optical device

    JP2012158664A